Clinical Features and Histopathological Findings in Rhupus Patients Developing Glomerulonephritis in Arzobispo Loayza Nacional Hospital Between 2003 and 2009 - Suárez Pichilingue, Gissela (2011)
Up to 10% of patients with Systemic Lupus Erythematosus have a joint condition similar to that of rheumatoid arthritis, which is called Rhupus. These patients predominantly have signs and symptoms of rheumatoid arthritis and kidney damage associated with Lupus. Objectives: To describe the clinical characteristics and the renal histopathological findings in patients with rhupus. Materials and methods: Retrospective review of case reports and kidney biopsies from patients seen from 2003 to 2009 in Arzobispo Loayza National Hospital. Results: There were 7 patients with rhupus; their median age was 40 years, the median time of disease progression was 2 years. Most relevant renal histopathological findings were type IV glomerulonephritis in 5 patients; proteinuria between 288 to 2560 mg/24 hours and rheumatoid factor titers between14 to 34.6 UI/L were also found. Conclusions: Patients were older compared to others previously reported previously in the literature. Lupus-related renal damage was moderate to severe.